2021
DOI: 10.1093/jn/nxab125
|View full text |Cite
|
Sign up to set email alerts
|

The American Rescue Plan Act Is a Great Start but More Increases in Supplemental Nutrition Assistance Program (SNAP) Benefits Are Likely Needed Due to Implicit Hidden Reductions

Abstract: The Supplemental Nutrition Assistance Program (SNAP) is intended to help low-income individuals reach the cost of a nutritious diet. In response to the Coronavirus disease 2019 (COVID-19) pandemic, SNAP benefits have been increased by 20.3% since October 2020. Given the intended goal of the program, is the 20.3% increase enough? Even prior to COVID-19, the literature had identified 3 separate shortcomings in the current formula that had not been addressed. Here, these shortcomings are integrated into a unifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…While most of the participants were recipients of at least one nutrition assistance program, their participation in these programs alone was not enough to ensure adequate access to healthy foods at all times. It has been suggested that SNAP benefits only provide about 41% of the adjusted cost of a healthy diet [28]. Moreover, on average, SNAP recipients redeem greater than 75% of their benefits by the middle of the month [29].…”
Section: Discussionmentioning
confidence: 99%
“…While most of the participants were recipients of at least one nutrition assistance program, their participation in these programs alone was not enough to ensure adequate access to healthy foods at all times. It has been suggested that SNAP benefits only provide about 41% of the adjusted cost of a healthy diet [28]. Moreover, on average, SNAP recipients redeem greater than 75% of their benefits by the middle of the month [29].…”
Section: Discussionmentioning
confidence: 99%
“…While research on FI during the pandemic is limited, this should not prevent us from considering policy efforts to lessen the gravity of FI amidst the present-day pandemic. Pre-pandemic research revealed SNAP benefits is not enough to alleviate FI as much as they could if they were to account for variation in food costs across the U.S. [3,13,21,31]. Moreover, federal efforts should further expand SNAP benefits beyond the current 20.3% increase, in response to the unique challenges presented by the pandemic [3,13,21,31].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-pandemic research revealed SNAP benefits is not enough to alleviate FI as much as they could if they were to account for variation in food costs across the U.S. [3,13,21,31]. Moreover, federal efforts should further expand SNAP benefits beyond the current 20.3% increase, in response to the unique challenges presented by the pandemic [3,13,21,31]. It is also important to consider alternative strategies that may promote food security for those at risk, especially in times of widespread food shortages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation